Facilitating forests of learning: Enabling an adaptive collaborative approach in community forest user groups: a guidebook - McDougall, C.; Pandit, B.H.; Banjade, M.R.; Paudel, Krishna Prasad; Ojha, H.; Maharjan,M.; Rana, S.; Bhattarai, T.; Dangol, S. (Center for International Forestry Research, 2009)
In this guidebook, we share suggestions for how a team of facilitators and a community forest user group (CFUG) can catalyse and maintain an approach to governance and management that draws on and strengthens the CFUG’s own adaptive and collaborative capacities. This approach fits within the Community Forestry framework and supports CFUGs in addressing two fundamental challenges: equity and the generation of livelihood benefits. In our experience, active and thoughtful facilitation of this approach can help CFUGs make their governance more inclusive, address tensions within the group, create more active groups with greater shared ownership of the community forest, and spark more livelihood generation activities, including for the poor. The transition to such an approach is not an easy or straight path: it involves changing relations and perspectives. Groups and their facilitators may use the suggestions in this book to help guide them as they travel on their journey, but the choices and steps are ultimately their own. Similarly, the specific outcomes of the change will be unique in each context. But this is also a strength: just as every CFUG is unique and everchanging, so its aspirations and its optimal strategies of governance and management will also be unique and ever-changing. We sincerely hope that this guidebook will prove useful to you in your own community forestry journey.